The law on cruelty to women and dissolution of marriages - Bangladesh; Matin, Abdul, 1945- (Dhaka : Madole Prokashani, 1992)
Subject compilation of Bangladesh act and ordinance; includes comments.
Keywords: Dowry -- Bangladesh -- Criminal provisions; Women -- Crimes against -- Bangladesh